2019
DOI: 10.1002/clc.23143
|View full text |Cite
|
Sign up to set email alerts
|

A clinical, proteomics, and artificial intelligence‐driven model to predict acute kidney injury in patients undergoing coronary angiography

Abstract: Background Standard measures of kidney function are only modestly useful for accurate prediction of risk for acute kidney injury (AKI). Hypothesis Clinical and biomarker data can predict AKI more accurately. Methods Using Luminex xMAP technology, we measured 109 biomarkers in blood from 889 patients prior to undergoing coronary angiography. Procedural AKI was defined as an absolute increase in serum creatinine of ≥0.3 mg/dL, a percentage incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 38 publications
0
36
1
Order By: Relevance
“…As AKI tends to occur in patients with common risk factors and in certain medical setting, risk prediction [53,[76][77][78]. Especially, Kashani et al tested the predictive value of novel urine biomarkers, TIMP-2 and IGFBP7, with ICU patients, and suggested a clinical model to predict the risk of AKI [37].…”
Section: The Important Role Of Noble Biomarkers In Aki Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As AKI tends to occur in patients with common risk factors and in certain medical setting, risk prediction [53,[76][77][78]. Especially, Kashani et al tested the predictive value of novel urine biomarkers, TIMP-2 and IGFBP7, with ICU patients, and suggested a clinical model to predict the risk of AKI [37].…”
Section: The Important Role Of Noble Biomarkers In Aki Prediction Modelsmentioning
confidence: 99%
“…Although the study had limitations regarding AKI risk prediction, as their main goal was to incorporate new urinary markers as risk factors, the study showed that the inclusion of novel biomarkers could improve the robustness of a prediction model in early periods of critical care. Although there is no consensus regarding using such biomarkers to predict AKI, several have shown promising results [37,53,[78][79][80]. Therefore, a novel biomarker that directly reflects kidney injury may further improve prediction in the future.…”
Section: The Important Role Of Noble Biomarkers In Aki Prediction Modelsmentioning
confidence: 99%
“…They used an original confounder-controlled cross validation procedure for robust generalization estimation. Ibrahim et al, [11] used a statistical approach leveraging LASSO attribute selection and Monte-Carlo cross validation simulation to identify variables predictive of acute kidney injuries using proteomics data. The work by Adam et al, [3] indirectly tackles the question of machine learning.…”
Section: Trend 1: Approaches Based On Machine-learning Methodsmentioning
confidence: 99%
“…Ibrahim et al developed a clinical and proteomics AKI risk predictor with an ML approach (least absolute shrinkage and selection operator (LASSO) with logistic regression) in a prospective study of 889 patients undergoing coronary angiography [106]. The risk predictor included a history of diabetes, blood urea nitrogen/creatinine ratio, c-reactive protein, osteopontin, CD5 antigen-like, and Factor VII and had an AUROC of 0.790 for predicting procedural AKI [106].…”
Section: The Era Of Artificial Intelligencementioning
confidence: 99%